Performa Pertumbuhan dan Kelulushidupan Pada Pembesaran Ikan Lele Mutiara (Clarias Gariepinus) di Balai Pembenihan Ikan (BBI) Lokal Kota Pontianak - Januardi, Uray; Masnita, Masnita; Fikri, Muhammad Zakiyul (PAKIS JOURNAL INSTITUTE, 2024)
The purpose of this study was to measure growth performance in pearl catfish rearing activities. To measure growth performance in this study, using variables of fish weight growth, specific growth rate, relative growth rate, and survival rate. In addition, water quality parameters were also measured, where the parameters measured were temperature, pH and DO. To obtain values ​​for these variables, fish weight measurements were carried out every 2 weeks and the initial weight of the fish stocked was 4 grams. Based on the results of the analysis of the data obtained, it shows that the growth of fish weight from the beginning of stocking to the 14th week reached 155.31 grams; specific growth rate is 1.584%; relative growth rate of 0.396%; and survival rate of 78%. Meanwhile, the water quality parameters, namely temperature, have an average value of 29 ℃. Then the pH value is at 8 and the DO value reaches 4.25 mg / L. The value of these three water quality parameters still meets the standards for catfish farming activities. And for its growth performance from the weight growth variable shows quite significant results for its weight gain. The survival rate value shows a fairly high value of 78%.